2009
DOI: 10.1002/adma.200900550
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Oxygen/Water Redox Couple in Suppressing Electron Conduction in Field‐Effect Transistors

Abstract: The back-gated field-effect transistor (FET) configuration has been central to the study of the electronic transport properties of organic and nanoscale materials. [1][2][3] Three-terminal transport measurements using this geometry are facilitated by using a degenerately doped silicon wafer covered with a thin silicon oxide layer as the substrate. It has been widely assumed that the substrate did not influence the measurement of the intrinsic properties of the material under study. However, Chua et al. [4] rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
292
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(320 citation statements)
references
References 35 publications
25
292
0
3
Order By: Relevance
“…The discussions above relate the resistance of the SWNTs to the heating power imparted into the SWNTs. Although s-SWNTs are generally more resistive than m-SWNTs, unintentional doping 51,52 and other effects can diminish these differences. Selectivity in such cases can be greatly enhanced by the Schottky barriers that form at the contacts between the antenna metal and the s-SWNT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discussions above relate the resistance of the SWNTs to the heating power imparted into the SWNTs. Although s-SWNTs are generally more resistive than m-SWNTs, unintentional doping 51,52 and other effects can diminish these differences. Selectivity in such cases can be greatly enhanced by the Schottky barriers that form at the contacts between the antenna metal and the s-SWNT.…”
Section: Resultsmentioning
confidence: 99%
“…53). In practice, s-SWNT often are unintentionally doped (for example, oxygen or water) 17,51 , in a way that shifts the Fermi level towards the valence band, to favour hole transport (schematic of band diagram in Supplementary Fig. 15a).…”
Section: Resultsmentioning
confidence: 99%
“…The gate leakage current was always found to be at least two orders of magnitude lower than the channel ON current, while the small operating hysteresis is attributed to atmospheric oxidants/adsorbates that are present even within the nitrogen glovebox, albeit at relatively small concentrations (~ppm). [39,40] Finally, the resulted electron and hole mobility values extracted are ~0.03 cm 2 V -1 s -1 and ~0.02 cm 2 V -1 s -1 respectively.…”
Section: (75) Swnt Field-effect Transistorsmentioning
confidence: 99%
“…The charge transport properties of the as-spun (7,5) SWNT networks were also characterized using a bottom-gate, bottom-contact transistor architecture fabricated on Si ++ /SiO2 (400 nm- Previous reports [39][40][41] have in fact shown that n-type conduction is suppressed in most organic semiconductor-based transistors due to charge traps from the SiO2 interface and especially due to charge transfer to the oxygen/water layer that is strongly bound to the SiO2 surface, where the H2O/O2 redox couple occurs. This is particularly important for SWNTs since the valence band position of the (7,5) SWNT (EV ≈ -5.2 eV) lies very close to the redox potential of oxygen (EREDOX ≈ -5.3 eV) dissolved in slightly acidic water (pH = 6) adsorbed on the SiO2 surface.…”
Section: (75) Swnt Field-effect Transistorsmentioning
confidence: 99%
See 1 more Smart Citation